Kebebasan Pers Serta Kritik Masyarakat Dalam Masa Pemerintahan Orde Baru - Ariwianto, Edwin (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2023)
Criticism is an essential component of any democratic system, serving as a means for the public to hold their leaders accountable. In Indonesia, which upholds democratic principles in its governance, the role of criticism has evolved significantly over time. During the era of President Soeharto, the freedom of the press was severely restricted due to government intervention and Soeharto's authoritative control over media outlets. This suppression of the press stifled dissent and prevented many criticisms from reaching the government, creating an environment where public discourse was heavily censored. The situation changed dramatically following Soeharto's resignation in 1998, which marked the end of the New Order regime. The subsequent reformation era brought about significant changes in the governmental structure, including the restoration of press freedom. This newfound freedom enabled the media to serve as a platform for public criticism and fostered a more open and transparent dialogue between the government and the citizens. This review delves into the impact of press freedom on government criticism in post-New Order Indonesia. By analyzing various literature sources and academic journals, it aims to explore how the re-establishment of press freedom has influenced the development and expression of public criticism toward the government, ultimately contributing to a more democratic society.